The Cambridge encyclopedia of language - Crystal, D. David Crystal (Cambridge: Cambridge University Press, 2010)
The Cambridge Encyclopedia of Language incorporates the major developments in language study which have taken place since the mid 1990s. Two main new areas have been added: the rise of electronic communication in all its current forms from email to texting, and the crisis affecting the world's languages, of which half are thought to be so seriously endangered that they will die out this century.
Includes bibliographical references and indexes.
Keywords: Language and languages -- Dictionaries; Linguistics -- Dictionaries